Epidemiological study on prosthodontic Aapliance deliveries within elderly cohorts in the Republic of Croatia, 2002–2006 - Bergman Gašparić, Lana (Array, 2009)
Abstract: Number of the dentate subjects among the elderly is dramatically increasing, as is the elderly proportion in overall population. Such trends indicate more need for prosthodontic appliances in elderly. The aim of this investigation was to determine the distribution of various prosthodontic appliances in older age cohorts, subventioned by the Croatian Institute for Health Insurance. Data on various prosthodontic appliances subventioned by the CIHI and delivered in all Croatian districts in the period 2002–2006 was obtained and statistically analyzed relative to 4 age cohorts of 50 and more years. The oldest age cohort (80+) showed the least appliance deliveries. The most frequently delivered appliance in all age groups were partial removable dentures (382 456 deliveries). Significantly less deliveries in the oldest age cohort compared to other groups (p<0.05) suggest that the oldest elderly patients tend to maintain prosthodontic appliances for a longer period than functionally acceptable